Pengaruh Penggunaan Serat Eceng Gondok (Eichhornia Crassipes) terhadap Karakteristik Beton Serat - Edowinsyah Edowinsyah; Mifthahul Bagas Thampinari; Vike Itteridi (Universitas Batanghari Jambi, 2026)
Concrete has a major weakness in the form of low tensile strength, making it prone to cracking when subjected to tensile loads. Generally, this weakness is overcome by adding steel reinforcement or fibers. In the city of Pagar Alam, water hyacinth (Eichhornia crassipes) grows abundantly in the waterways and causes environmental pollution. This study aims to optimize water hyacinth waste as an additional material for concrete to enhance its tensile strength. Fiber-reinforced concrete was produced with varying additions of water hyacinth fibers at 0%, 2%, 2.5%, and 3% of the cement weight, with fiber lengths of 6 cm. The tests conducted included slump tests, specific gravity, compressive strength, and flexural strength. The results showed that normal concrete (BN) had the highest compressive strength, at 19.11 MPa at 28 days. Meanwhile, concrete with 3% fiber (BS3) yielded the highest flexural strength, at 4.76 MPa at 28 days. In conclusion, the addition of water hyacinth fibers can enhance flexural strength, although it does not significantly affect compressive strength. Thus, water hyacinth fibers have the potential to serve as an environmentally friendly alternative to reduce waste while improving concrete characteristics.